2014
DOI: 10.1002/bult.2014.1720400612
|View full text |Cite
|
Sign up to set email alerts
|

Metadata use in research data management

Abstract: EDITOR'S SUMMARY Prompted by federal requirements, academic institutions and librarians have become more involved in data management planning. An e‐research implementation group was formed at the University of Illinois to develop and promote data initiatives in a variety of ways, including updating a data management website to provide education and awareness to students and faculty. Part of the site focuses on documentation and metadata, describing traditional and nontraditional data types and sources, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
2
Order By: Relevance
“…They were, of course, concerned about the storage of their data. The researchers believe that they need to focus on their research work and the work of organizing and preserving data for sharing, and reuse gets relegated (Wiley, 2014). Tenopir et al (2011) reported that the researchers are content with their short-term data storage but not satisfied with the storage options available for the long term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were, of course, concerned about the storage of their data. The researchers believe that they need to focus on their research work and the work of organizing and preserving data for sharing, and reuse gets relegated (Wiley, 2014). Tenopir et al (2011) reported that the researchers are content with their short-term data storage but not satisfied with the storage options available for the long term.…”
Section: Discussionmentioning
confidence: 99%
“…The metadata has a pivotal role in data management and sharing. It helps the researchers describe their datasets appropriately and facilitate others to search and retrieve them (Wiley, 2014).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Además, los metadatos están configurados y son implementados en los sistemas computacionales que son utilizados mediante el uso de programas informáticos, como es el caso de los destinados al desarrollo de repositorios de datos. Pietritch (2017) y Wiley (2014) han abordado la función de los metadatos en el proceso integral de la gestión de los datos de investigación, destacando la importancia de organizar eficientemente a los datos para propiciar su búsqueda y acceso.…”
Section: Findability=encontrabilidadunclassified
“…La reutilización de los contenidos digitales es muy importante, entre otros motivos (además de los recogidos en el apartado C.1), porque evita la duplicidad de esfuerzos en la generación de materiales educativos (Alemu, Stevens, & Ross, 2012;C. Wiley, 2014).…”
Section: C3 Reutilización De Los Rea Y Contenidos Digitalesunclassified